New Records of Mantis Shrimps (Crustacea: Stomatopoda) from the Gujarat Waters, India - VADHER, PIYUSH; KARDANI, HITESH; BELEEM, IMTIYAZ (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Mantis shrimps are the most significant predators in the shallow waters and intertidal regions of tropical and subtropical marine ecosystems and they are integral components of the food chain. Additionally, mantis shrimps are sensitive to environmental pollutants and indicate poor environmental conditions through their ecological behaviour. As a fisheries species, they hold immense socio-economic importance for several countries. In this study, we document three species of stomatopods found in the waters of Gujarat, India. Notably, Manningia arabica (Manning, 1990), which is rare and endemic to the Arabian Sea, is reported for the first time in Indian waters. Furthermore, Alimopsis supplex (Wood-Mason, 1875) and Oratosquillina quinquedentata (Brooks, 1886) are also documented for the first time in the waters of Gujarat. The study includes taxonomic descriptions, habitat characteristics, and geographical distribution information for each of these species.